enter image description here

If I want to do the following transform $$x[(n-1)^2]$$

I have thought about substituting each value of $n$ in $x[n]$ according to $x[(n-1)^2]$

i.e at $n=0, x[0]=1$ to put it in $x[(n-1)^2]$

$x[(0-1)^2] = 1$ and so on...

Am I right ? and if I am at $n=-4$ it will be replaced at $n=25$

  • 3
    $\begingroup$ at $n=4$ you should transform it to $n'=(4-1)^2 = 9$, so that $y[4]=x[9]$ This is effectively a nonuniform sampling performed on $x[n]$ to produce $y[n] = x[(n-1)^2]$, on the other hand at $n=-2$ the new index will be $n'=(-2-1)^2=9$ so that $y[-2]=x[9]$ again, i.e. $y[n]$ will be even symmetric about $n=1$, based on its definition. $\endgroup$ – Fat32 May 25 '16 at 2:28
  • $\begingroup$ that means at $n=-4$ $x[(-4-1)^2] = 25$. Is that corerct? $\endgroup$ – Hossam Houssien May 25 '16 at 14:52
  • $\begingroup$ No , that is quite not the case, for the sample index $n=-4$, you have the following relationship between $y[n]$ and $x[n]$ as: $y[-4] = x[(-4-1)^2]=x[25]$. Hope this is enough to see what it means. (i.e. index $n=-4$ of y[n] is transformed into index n'=(-4-1)^2=25 of x[n']) $\endgroup$ – Fat32 May 25 '16 at 15:11
  • $\begingroup$ $x[n]$ is the transformed signal, while $y[n]$ is the original signal , is that what you meant? and do you meant what happens at $y[-4]=-1$ happens at $x[25] =-1$ $\endgroup$ – Hossam Houssien May 25 '16 at 15:27
  • $\begingroup$ $x[n]$ is the original signal and $y[n]$ is new signal which is defined based on $x[n]$, by transforming the argument $n$ of $x[n]$ into $(n-1)^2$. So in effect $x[n]$ is transformed into $y[n]$. Your second cliam is right. $\endgroup$ – Fat32 May 25 '16 at 16:00

This is what I came up for using the table below. IF anyone can confirm?**

$$ \begin{array}{c|c|c} n & (n-1)^2 & x\left[(n-1)^2\right] \\ \hline -2& (-2-1)^2=9\ & x[9]=0 \\ -1& (-1-1)^2=4\ &x[4]=0\\ 0& (0-1)^2=1& x[1]=1\\ 1&(1-1)^2=0& x[0]=1\\ 2& (2-1)^2=1& x[1]=1\\ 3& (3-1)^2=4& x[4]=0\\ 4&(4-1)^2=9& x[9]=0 \end{array} $$

  • $\begingroup$ confirmed ! :)) $\endgroup$ – Fat32 May 25 '16 at 22:54

as addition for Houssam's answer, we can see that for every "n" value from the graph P1.22, we replace $n$ in order to find $N$ by the relation $N=(n-1)^2 \implies x[(n-1)^2]= x[N]$ ,so we find that for $n=0,1,2 \implies x[N]=1$. And $0$ elsewhere (depends on figure p1.22) so now we represent $x[(n-1)^2]$ as :

[x[(n-1)²] graph [1


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.